Emission of volatile halocarbons from selected species of tropical seaweeds / Fiona Keng Seh Lin - Fiona Keng , Seh Lin (2021)
Marine emissions of short-lived biogenic halocarbons affect atmospheric composition and chemistry. Research has shown that seaweeds emit these halocarbons into the seawater and air. The presence of these gasses could affect local weather while contributing to the global halocarbon load, possibly causing stratospheric ozone loss. This is especially evident in the tropics due to the existence of vertical transport that could affect the global circulation of these compounds in the atmosphere. There is a lack of information on the contribution of tropical seaweeds to the global halocarbon budget. This is of concern especially under a changing climate. This study was formulated to investigate the response of tropical seaweeds to variable environmental conditions, in terms of halocarbon emissions. In addition, seaweeds cultivated using three different systems were studied. Laboratory studies were conducted for investigating the effect of temperature (20–40 °C) on the halocarbon emission by Gracilaria manilaensis, Ulva reticulata, Kappaphycus alvarezii and Turbinaria conoides and the combined effect of temperature (25–34 °C) and irradiance (0–177 μmol photons m-2 s-1) on the halocarbon emission by K. alvarezii. Higher temperature results in decreased emissions of CHBr3, CH2Br2 and CH2I2 (r = (−0.69)–(−0.95); p< 0.01) in most seaweeds. The combined effect of irradiance and temperature significantly affect the emission of halocarbons by K. alvarezii, with stronger association to temperature. Of the three cultivation systems, the amount of halocarbon released by G. manilaensis especially CH2Br2 was found to be the highest in the cage culture in the river mouth, followed by the offshore platform and tank culture. Daylight emissions by G. manilaensis from both onshore and offshore cultivation systems was 10 to 52 times greater than in the dark, while emissions by K. alvarezii were between two and five times greater during the day. Halocarbon emissions by G. manilaensis was positively affected by temperature, irradiance and seawater phosphate level during cultivation. Negative correlations were found between ammoniacal nitrogen, nitrate and nitrite levels with the CH2Br2 emitted by K. alvarezii. Estimation from this study showed that the harvesting activity of K. alvarezii in year 2017 in Malaysia could release 72–360 mol Br hr-1; a value that is slightly higher than the estimated value derived from previously predicted flux rate estimated from wild Malaysian seaweeds. Under laboratory-controlled conditions, K. alvarezii releases higher amount of halocarbon. However, in situ studies revealed that G. manilaensis emits higher amount of halocarbon due to the fluctuations in the environment. In light of the impending climate change with a likely rise in temperature, seaweed farming has the potential to be expanded to the subtropical waters which could bring about increased emissions of halocarbons. In summary, halocarbons including the highly emitted CHBr3 and CH2Br2 was found to be emitted by the selected wild and farmed tropical seaweeds. Although the emissions were species-dependent, the emission of these compounds were found to be closely associated to changes in environmental parameters such as temperature, irradiance, and seawater nutrients.